Strengthening The Role Of Youth Association (Karang Taruna) In Sustainable Waste Management Through Digital Literary, Waste Bank, And 3R TPS (Waste Management Site) - Prasetyani, Henny; Diah Nugraheni; Tangguh Prakoso (Edumedia Solution, 2025)
Waste issues pose a challenge in the environmental sector, especially in rural areas. Low public awareness of sustainable waste management demands the active involvement of youth as agents of change. This community service program aims to strengthen the role of youth organizations in sustainable waste management through digital literacy, the establishment of waste banks, and the optimization of the management of the 3R (Reduce, Reuse, Recycle) TPS. Activities are carried out through training, mentoring, and participatory actions involving 10 youth organizations and 20 local residents. Quantitative results show a 60% increase in digital literacy competency, a 45% increase in community participation in waste sorting, and a 50% increase in the effectiveness of 3R TPS management. This program has successfully empowered youth organizations as digital-based environmental education agents and strengthened the sustainable integrated waste management system at the village level.